Non-communicable disease management: Access to healthcare during COVID-19 pandemic in rural Kerala, India - J. Revu; Marthada Pillai Anand; Rafi Aadil; G.K. Mini (Elsevier, 2023)
Background: Globally, data on the coronavirus disease (COVID-19) pandemic showed a higher risk of infection and complications in people with non-communicable diseases (NCDs). In India, the prevalence of NCDs and their risk factors vary significantly between states. Compared to other states, Kerala has the highest prevalence of non-communicable diseases in the country, along with the highest proportion of the elderly population. The study evaluates the disease management patterns and changes in healthcare behaviors among adults with NCDs in Kerala during the COVID-19 pandemic. Methods: A cross-sectional study was conducted among 410 adult NCD patients in rural Thiruvananthapuram district, Kerala. Using a semi-structured interview schedule, the present study gathered information on socio-demographic characteristics, disease patterns, healthcare utilization, and behavioral change during the pandemic. Results: Mean age of the participants was 62 years (range: 37-88; women: 64%). The most prevalent NCD was hypertension (74%) and diabetes (65%) followed by chronic respiratory disease (12%), cardiovascular disease (11%), and cancer (2%). Nearly 76% had difficulty in obtaining consultation/medical follow-up. Around 10% relied on telecommunication and 32% reported increased stress during the pandemic. Those with low socio-economic status and with a single NCD were more vulnerable to the challenges faced during the pandemic. Conclusion: A higher proportion of adults with NCDs faced difficulties in healthcare access and had negative healthcare behaviors during the pandemic. The findings highlight the need to ensure better healthcare for people living with NCDs during the times of pandemic.